Integration of Islam and Pendhalungan Cultural Values as an Umbrella Attitude Religious Tolerance - Ilfiana Firzaq Arifin; Akhmad Arif Musaddad; S Sudiyanto (ADDIN, 2018)
Diversity is the initial trigger of changing attitudes among individuals. The attitude change can be negative or positive, depending on each individual whether to menfilter anything that indicates the creation of a change of attitude towards a positive or negative. Writing this article aims to provide an overview of male and female students of SMK Plus Nurul Ulum were able to create a positive change in attitude towards the tolerance with teachings based on Islamic religious and cultural values Pendhalungan. The method used in this study is a qualitative method that is by conducting indepth interviews with some of the parties in the relevant schools. Then the data were also obtained from journals and literature support.